A copa do (a) capital - Brasil, Vinicius de Moraes (2015)
This study aimed to identify the political role of mega sports events in Brazil from the analysis of cropping on the Soccer World Cup in 2014 aiming to understand the links and present relations between this government policy and the need to expand the subordination of the country to the capital monopolist. For this we rely on the understanding that this political project of domination imposed on Brazil by the world bourgeoisie shows clear signs of exhaustion , with the June days of 2013 signaled this. Therefore we investigated the popular manifestations and its set of claims relating the content demands of the Brazilian people with government policies expressed in hosting the games , trying to understand the continuity of this struggle and its development during the popular demonstrations against the FIFA World Cup in Porto Alegre, Fights organized by Block by Public Transport.